Refugee Quota Trading within the Context of EU-ENP Cooperation: Rational, Bounded Rational and Ethical Critiques - Mollie Gerver (Journal of Contemporary European Research, 2013)
In 1997 Peter Schuck proposed a ‘refugee quota trading’ mechanism, whereby countries voluntarily form a union, each country accepting a quota of refugees and able to buy and sell the quota to other states within and even outside of the union. Today, the EU arguably has a de facto cash transfer mechanism both within the EU and between the EU and European Neighbourhood Policy countries. This article explores the question of refugee quota trading, explaining why current EU policy fails to increase refugee protection. Throughout the critique, states are treated either as rational actors or actors with present-preference bias, the latter largely ignored in current discussions on international refugee ‘burden sharing’. In addition, the ethics of refugee quota trading is presented using arguments distinct from that of Anker et al. (1998) who argue that refugee quota trading creates a ‘commodification’ of refugees. One could argue that refugees’ protection is being commodified, not refugees themselves. However, when states are provided funds not to deport refugees, this can be a type of reward for not taking an action that states ought to follow regardless of the reward. Just as there are non-utilitarian reasons not to rely on rewards alone for lowering the crime rates for heinous crimes within states, there may be non-utilitarian arguments against refugee quota trading.